Myocardial revascularization in patients with coronary heart disease and type 2 diabetes - Natalya A. Bezdenezhnykh (Endocrinology Research Centre, 2016)
The review discusses myocardial revascularization in patients with coronary heart disease and type 2 diabetes. The data presented include findings from recent research and international and national recommendations and provides evidence on the advantages of coronary artery bypass surgery over percutaneous coronary intervention for patients with diabetes mellitus, stable coronary artery disease and multiple coronary artery lesions. Type 2 diabetes remains a significant predictor of adverse long-term outcomes of coronary artery bypass surgery. Therefore, we review studies showing that different strategies of coronary revascularization and preoperative preparation can affect the results of coronary intervention in patients with diabetes.